New botanical discoveries in Eugenia (Myrtaceae) from Bolivia and Brazil - Villarroel, Daniel; Faria, Jair E. Q.; Belmont, Aléxia Moraes; Gomes, Sueli Maria; Proença, Carolyn E. B. (Phytotaxa, 2016)
Eugenia michaelneei is a new Bolvian species endemic to the Meseta de Chochís and the Serranía de Santiago de Chiquitos in eastern Santa Cruz Department. It is closely related to E. sonderiana, but differs mainly by its small height, low number of secondary veins, midvein glabrescent on the abaxial surface and glabrous on the adaxial surface, and few ovules per locule. Nineteen differences in their leaf anatomy were also recorded although they share a dorsiventral mesophyll. Eugenia repanda and E. corrientina are reported as new occurrences for Bolivia and Brazil respectively.